Uneven impacts and uncoordinated studies: A systematic review of research on unconventional oil and gas development in the United States - Walsh, Kathryn Bills; Haggerty, Julia Hobson; Jacquet, Jeffrey B.; Theodori, Gene L.; Kroepsch, Adrianne (Energy research & social science, 2020)
The unconventional oil and gas (UOG) boom in the United States produced a surge of social science research activity about the industry's local impacts, the vast majority of which relied on local stakeholders to contribute data. Like UOG development across the United States, research on the local impacts of UOG has been geographically dispersed and uneven and mostly uncoordinated. The primary purpose of this systematic review of peer-reviewed articles and theses and dissertations is to provide an overview of the timing, spatial distribution, and methods used in research on local impacts of UOG development since 2000. The study identifies 167 unique human subject data collection efforts in U.S. UOG locations between 2000 and 2018. This overview—along with analysis of response rates and recruitment and engagement patterns—reveals risks that the recent boom in impacts research may have contributed to research fatigue on the part of some human subject research participants. The study also demonstrates challenges in deriving generalizable observations from local impacts research. Both problems are associated with the uneven geographic distribution of research across UOG locations in the U.S., researchers’ tendency to arrive at the height of development activity, inconsistent and incomplete reporting on methods in publications, and an over-reliance on accessible research subjects. Future research and scholarly reflection should evaluate constraints and factors that influence research strategies. In the meantime, the U.S. research community faces an imperative to consider opportunities to enhance and coordinate research activities in energy communities.